Investigation of the role of the stock market in the creation and development of innovative firms (Путеводитель предпринимателя)
In article form a profile of the Russian innovation companies, as well as the analysis of the structure of sources of investment financing. The role of the stock market as a source of financing of innovative companies. The influence of the market of investments and innovations in the formation of innovative firms.